Do the individuals closest to internet firms believe they are overvalued - Schultz, P (Journal of Financial Economics, 2001)
Two explanations are commonly offered for the large number of recent IPOs by Internet firms. The first argues that Internet firms are trying to grab market share in an industry with large economies of scale. The second argues that Internet firms are rushing to go public when Internet stock prices are irrationally high. In this paper we examine the actions of those closest to Internet firms – firm managers, underwriters, and venture capitalists – to determine their motives for going public. Numerous strategic alliances and mergers and acquisitions provide strong evidence of a rush to grab market share. Other factors provide only weak evidence that Internet IPOs are attempts to sell overpriced stock.